Assessing the Differential Effects of Race and Ethnicity on Sentence Outcomes Under Different Sentencing Systems. (February 2013) - Wang, Xia; Mears, Daniel P.; Spohn, Cassia; Dario, Lisa
Although many states have adopted sentencing guidelines, questions remain about whether guidelines achieve one of their primary goals—reducing disparities that arise from such extralegal factors as race and ethnicity. To date, research has not taken a cross-state approach to testing for racial or ethnic disparity in sentences imposed in guideline and nonguideline states or to examining whether less disparity exists in states with voluntary or presumptive guidelines. To address this research gap and inform sentencing scholarship, data from the State Court Processing Statistics program are used to determine whether offenders' race or ethnicity affects incarceration and sentence length decisions in jurisdictions with different types of sentencing systems. Implications of the findings for theory, research, and policy are discussed.